The Facts on File dictionary of proverbs - Manser, Martin H. (Facts on File library of language and literature., 2002)
"The English language is enhanced by thousands of proverbs that make observations, impart life lessons, or give advice. With more than 1,500 entries, this dictionary explains the meanings and origins of short, memorable sayings that are widely recognized today, such as art is long and life is short; conscience does make cowards of us all; gather ye rosebuds while ye may; Homer sometimes nods; and still waters run deep.".